Infecção pelo HIV, hepatites B e C e sífilis em moradores de rua, São Paulo HIV infection, hepatitis B and C and syphilis in homeless people, in the city of São Paulo, Brazil - Valquiria O. C. Brito; Deolinda Parra; Regina Facchini; Cassia Maria Buchalla (Universidade de São Paulo, 2007)
OBJETIVO: Estimar a prevalência das infecções pelo HIV, vírus das hepatites B e C, e da sífilis em moradores de rua. MÉTODOS: Estudo transversal com intervenção educativa, realizado no município de São Paulo, de 2002 a 2003. Selecionou-se amostra de conveniência de moradores de rua que utilizavam albergues noturnos, segundo os critérios: >18 anos e não apresentar distúrbios psiquiátricos. Em entrevistas, foram coletados dados sociodemográficos e de comportamento, e realizados exames laboratoriais para HIV, hepatite B e C e sífilis, e aconselhamento pós-teste. RESULTADOS: Participaram 330 usuários dos albergues, com 40,2 anos (média), 80,9% homens, nas ruas, em média, há um ano. Observaram-se prevalências de 1,8% de HIV, 8,5% de vírus de hepatite C, 30,6% de infecção pregressa por hepatite B, 3,3% de infecção aguda ou crônica pelo vírus hepatite B e 5,7% de sífilis. Uso consistente de preservativo foi referido por 21,3% e uso de droga injetável, por 3% dos entrevistados. A positividade para HIV foi de 10% e 50% para vírus da hepatite C entre usuários de drogas injetáveis, versus 1,5% para HIV e 7,3% para hepatite C nos demais, evidenciando associação entre esse vírus e uso de droga injetável. Prisão anterior foi referida por 7,9% das mulheres e 26,6% dos homens, com prevalência de 2,6% para HIV e 17,1% para vírus da hepatite C. CONCLUSÕES: As elevadas prevalências de HIV e vírus de hepatite B e C requerem programas de prevenção baseados na vacinação contra hepatite B, diagnóstico precoce dessas infecções e inserção dos moradores de rua em serviços de saúde. OBJECTIVE: To estimate the prevalence of HIV infections, as well as hepatitis B and C and syphilis viruses in homeless people. METHODS: Cross-sectional study with educational intervention, conducted in the city of São Paulo, between 2002 and 2003. A convenience sample of homeless people who used night shelters was selected, according to the following criteria: aged 18 or older and not showing psychiatric disturbances. During interviews, sociodemographic and behavioral data were gathered and HIV, hepatitis B and C and syphilis laboratorial tests and post-test counseling were carried out. RESULTS: A total of 330 shelter users participated, with an average age of 40.2 years, 80.9% of them male, having lived on the streets for one year in average. Prevalences of 1.8% for HIV, 8.5% for hepatitis C virus, 30.6% for previous hepatitis B infection, 3.3% for chronic or acute infection by hepatitis B virus, and 5.7% for syphilis. The consistent use of condoms was referred to by 21.3% of interviewees and the use of injecting drugs by 3% of them. Positivity was 10% for HIV and 50% for hepatitis C virus among injectable drug users, versus 1.5% for HIV and 7.3% for hepatitis C among the others, showing an association between the virus and the use of injecting drugs. Previous imprisonment was referred to by 7.9% of women and 26.6% of men, with a prevalence of 2.6% for HIV and 17.1% for hepatitis C virus. CONCLUSIONS: The high prevalences of HIV and hepatitis B and C viruses require prevention programs based on vaccination against hepatitis B, early diagnosis of these infections and placement of homeless people into health services.